RELATIONSHIPS BETWEEN INFORMATION TECHNOLOGY INFRASTRUCTURE AND INNOVATION ON PERFORMANCE OF BANKS IN MALAYSIA - Anita Ismail; Muhammad Shukri Bakar (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2017)
The current business environment has been characterized as hyper-competitive, especially for innovation sensitive products and services. This business environment forces organizations to be innovative and show fast responses to all the environmental changes. This situation urged banks to develop their competencies that encourage innovation and foresee future business opportunities. More specifically, banks, to keep pace with the new technological advancements and be able to keep in business, have to adopt innovative strategies that results in high levels of customers’ satisfaction. This research analyses the relationship between information technology infrastructure and innovation on the performance of the banks. Data for the empirical investigation originates from banks in Malaysia. The study will provide the empirical evidence of the following output: new findings and knowledge that benefited the researchers and managers at banks that emphasize the strategic importance of information technology infrastructure and innovation in the performance within the Malaysian banking institutions. The results of the analyses show that information technology infrastructure has a significant effect towards performance, while innovation showed an insignificant relationship with the performance. Thus, appropriate strategies are important to enhance their performance and ensure their survival, especially in these turbulent economic times